Determinan permintaan kredit konsumsi pada bank umum sebelum dan setelah pandemi di Indonesia - Fadila, Indah; Nurjanah, Rahma; Vyn Amzar, Yohanes (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2025)
This study aims to analyze the influence of the BI-Rate, Gross Domestic Product (GDP), and economic expectations (proxied by the Consumer Confidence Index/CCI) on the demand for consumer credit at commercial banks in Indonesia during and after the Covid-19 pandemic. The data used are quarterly secondary data from the 2018–2024 period, analyzed using the Error Correction Model (ECM) approach to examine both short-term and long-term relationships among variables. The results show that in the long term, the BI-Rate has a negative significant effect, GDP has a positive and significant effect, while CCI has a negative and insignificant effect on consumer credit demand. In the short term, only the BI-Rate has a positive and significant effect, whereas GDP and CCI do not show significant effects. These findings indicate that interest rates play a dominant role in directly influencing consumer credit demand in the short term, while economic growth demonstrates a more substantial impact in the long term. Meanwhile, consumer economic expectations, as reflected by the CCI, have not been proven to significantly influence consumer borrowing decisions.